USING LANDSAT IMAGERY AND VEGETATION INDICES DIFFERENCING TO DETECT MANGROVE CHANGE: A CASE IN THAI THUY DISTRICT, THAI BINH PROVINCE - Hai Hoa, Nguyen; Duy Binh, Tran (Journal of Forestry Science and Technology, 2016)
Using multi-temporal Landsat data and GIS technology to quantify changes in coastal mangroves is very important in terms of identifying drivers and providing scientific foundation for better mangrove management in Thai Thuy district, Thai Binh province. Vegetation indices, such as NDVI, SAVI, IPVI, DVI, SR, RVI is adopted as a suitable method to quantify and monitor the extents of mangrove this study. As a result, NDVI is the most accurate in comparison with other indices. Regarding historical changes in mangrove extents, overall mangrove extents during 2001- 2016 have increased by 538.5 ha. In particular, the period of 2001 - 2006 has evidenced with a slight increase of mangroves and continued to a considerable increase during 2006 to 2011, 454 ha of new mangrove extents created, while the period of 2011 - 2016 has experienced with an increase of mangrove extents with 80.3 ha. The main drivers of increase of mangrove extents are due to the effective mangrove rehabilitation and restoration programs. These findings imply that mangrove mangement is in a good place in Thai Thuy district and local people are better aware of the importance of mangroves. Based on the findings, the study has given a number of solutions for better manage mangroves extents in the study site.